PERKUATAN SEISMIK STRUKTUR RANGKA BETON BERTULANG MENGGUNAKAN BREISING BAJA TIPE X DAN V TERBALIK - Sukrawa, Made; Dharma Giri, Ida Bagus; Deskarta, I Putu; Prayoga, Made Hendra (JURNAL SPEKTRAN; Vol 4 No 2 (2016): Vol. 4, No. 2, Juli 2016DO - 10.24843/SPEKTRAN.2016.v04.i02.p10, 2016)
Abstract: Analysis of reinforced concrete frame with steel braces has been done to compare the behavior of the open frame structure with reinforced concrete structure with steel braces. Three models of 2D open frame structure with 3, 4 and 5 floors were made and analyzed in SAP2000 v17 with intermediate detailing according to Indonesian Codes for Seismic Load (SNI 1726: 2002). 3-span frame structure with a span length of 6 m and level height of 3,5 m were designed according to SNI 1726: 2002, and then re-analyzed with special detailing according to New Indonesian Codes for Seismic Load (SNI 1726: 2012). After that, it was added with braces as seismic retrofitting. Two types of braces (X and concentric inverted V) were used in this study and analyzed with conventional analysis and stage construction analysis according to their stages of implementation. From the analysis results, several structure components that analyzed according to SNI 1726:2012 provitions were experience over-stressed. After retrofitted with steel braces, those components fulfill strength provition according to SNI 2847:2013 about structural concrete regulations for buildings. In addition to that, displacements that occurs on braced frame are smaller than displacements of the open frame structure with ratio of 0.08, 0.12, and 0.18 for X-brace frames with 3,4, and 5 storey and 0.07, 0.11, and 0.16 for inverted-V brace. With staged construction analysis, displacements of  X-braced frame structure increased by 14.38%, 13.62%, and 9.98% from the conventional analysis results for structure with 3, 4,and 5 storey. For structure with inverted-V brace, displacements increased by 15.83%, 14.29%, and 10.09%.
Keywords: Stage Construction Analysis, Concentric Braces, Seismic Retrofitting